Neurobiology and genetics of behavioral addictions: a brief review - İzci, Filiz and Usta Sağlam, Nazife Gamze and Ergelen, Mine (Journal of Dependence, 2022)
Among behavioral addictions gambling disorder, sex, digital game, exercise, food, shopping and work addictions are similar to substance addictions at many points, including disruption in functionality, tolerance and withdrawal, comorbid diseases, genetic background and neuronal mechanisms. While neurobiological studies of behavioral addictions are very recent, research on biochemical, radiologic, genetic and treatment related features of behavioral addictions have revealed strong neurobiological associations with alcohol and substance addictions. Most of the studies in the literature focused on gambling addiction and internet addiction, but it is shown that beside their differences, there is also similar neurobiological and structural alterations exist in other behavioral addictions. It is important to recognize and understand behavioral addictions with their genetic and neurobiological aspects, to increase awareness of these disorders, to handle the process better and to develop prevention and treatment strategies. In this article, we reviewed data on the neurobiological and genetic manifestations and associated neurobiological pathways of behavioral addictions that are beginning to gain more attention from clinicians and researchers.